2014
DOI: 10.2147/ccid.s73302
|View full text |Cite
|
Sign up to set email alerts
|

Severity and impact of acne vulgaris on the quality of life of adolescents in Nigeria

Abstract: BackgroundAcne vulgaris is a common skin condition, which affects most adolescents at some point in their lives. It has been found to have a significant impact on their psychological well-being and has been associated with depression and suicide ideation. Many studies have assessed the impact of acne vulgaris on the quality of life (QoL) in different population subgroups around the world, but there is a dearth of reports from the African subcontinent. This study thus seeks to assess the severity of acne vulgar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
4
3
0
1
Order By: Relevance
“…We reported higher prevalence of AV by clinical examination compared to self-reported AV. This was similar to studies in other settings [17], where the prevalence of self-reported AV was lower compared to AV by clinical assessment. It is well known that patients’ perception of AV does not always correspond to the diagnosis made in clinical examination [2].…”
Section: Discussionsupporting
confidence: 90%
“…We reported higher prevalence of AV by clinical examination compared to self-reported AV. This was similar to studies in other settings [17], where the prevalence of self-reported AV was lower compared to AV by clinical assessment. It is well known that patients’ perception of AV does not always correspond to the diagnosis made in clinical examination [2].…”
Section: Discussionsupporting
confidence: 90%
“…This finding is concurrent with several other studies [1][2][3][4][5][6][7][8]. Studies conducted in Saudi Arabia reported that 64% of acne cases were mild, 30.1% were moderate, and only 5.9% were severe [12][13][14]. This finding is also consistent with findings from an Indian study, which indicated that Grade I acne was the most common, affecting 60.2% of participants However, a Chinese study found that 68.4% of acne patients had moderate acne.…”
Section: Discussionsupporting
confidence: 89%
“…According to a study conducted in Riyadh, more than half of the cases (57.5%) had first-degree acne. Mild acne was seen in 53% of patients in Egypt [9,[12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ketika remaja tidak menyukai diri mereka sendiri dan menganggap diri mereka buruk karena masalah penampilan mereka, mereka cenderung sangat fokus pada perubahan penampilan mereka dalam semua aspek atau hal-hal yang mereka lakukan dan lebih sensitif terhadap perasaan malu tentang penampilan mereka. Dalam hal ini, remaja cenderung sangat peduli dengan masalah jerawat mereka (Henshaw & Ogedegbe, 2014) bahkan dalam kegiatan yang tidak berhubungan dengan jerawat.…”
Section: Latar Belakangunclassified